Risks Identification In Construction Of Jetty Projects: Literature Review - Jatmiko Kurniawan; Kiki Patricia Dewi; Herman Irawan; Humiras Hardi Purba (Rekayasa Sipil, 2022)
Delays in project development often occur due to various risk factors that have not been identified during project implementation, resulting in increased project delays and unexpected costs. However, each construction project has different risks depending on the type of project and project environmental conditions, so it requires handling different project implementation methods.In a jetty project, risk assessment is carried out from both technical and non-technical perspectives. From a technical point of view, risks are assessed starting from soil conditions, water level, weather, installation methods, design changes, etc. Meanwhile, from a non-technical perspective, the risks arising from the environment, social and social aspects are assessed. economic, legal, and institutional aspects as well as finance and investment.This summary literature review shows that Technical Risk has the greatest impact on jetty projects in the internal and external project category.